Effect of Education and Health Infrastructure on Industrial Sector Performance:: Empirical Evidence from Nigerian Economy - Agum, Charles; Musa, Babayo (ABUAD Journal of Social and Management Sciences, 2023)
The purpose of this study is to empirically examine the impact of education and health infrastructure on industrial sector performance in Nigeria. In that vein, an annual time series dataset was generated from Central Bank Statistical Bulletin and World Development Indicators (WDI) for the period, 1980 to 2022. The study employed Autoregressive Distributed Lag Model to analyse the parameters. Ex-post facto research design was also adopted. The descriptive results suggest that all the variables have positive mean. The implication of the positive mean is that all the variables in the model recorded positive average growth rate during the period under review. The inferential analysis began with estimation of unit roots tests and the results revealed that variables were stationary at different orders of integration. Furthermore, the cointegration test shows that there is an evidence of cointegration among the variables. Based on the cointegration result, this study applied ARDL approach to generate the estimated short-run and long-run results. Based on the short-run estimate, this study reveals that there is positive but statistically significant relationship between education infrastructure and industrial sector performance. There is negative but statistically insignificant relationship between health infrastructure and industrial sector performance, while there is also a negative but statistically insignificant relationship between communication infrastructure and industrial sector performance.